Biological roles of piRNAs in colorectal cancer - Jing, Zhuang; Xi, Yang; Yin, Jin; Shuwen, Han (Gene, 2021)
Colorectal cancer (CRC) is one of the most common malignancies worldwide and a major cause of cancer-related deaths. Numerous studies have suggested that piwi-interacting RNAs (piRNAs), a new type of non-coding RNA (ncRNA), are closely related to the occurrence and development of cancer. piRNAs have been shown to regulate the occurrence of CRC by modulating multiple molecular signaling pathways. Here, the roles of piRNAs in CRC were reviewed to provide evidence for their potential as molecular targets for CRC.